In Vitro Activities of LTX-109, a Synthetic Antimicrobial Peptide, against Methicillin-Resistant, Vancomycin-Intermediate, Vancomycin-Resistant, Daptomycin-Nonsusceptible, and Linezolid-Nonsusceptible Staphylococcus aureus - Saravolatz, Louis D. (American Society for Microbiology, 2012)
LTX-109 and eight other antimicrobial agents were evaluated against 155 methicillin-resistant Staphylococcus aureus (MRSA) isolates, including strains resistant to vancomycin and strains with decreased susceptibility to daptomycin and linezolid, by microdilution tests to determine MICs. Time-kill assays were performed against representative MRSA, vancomycin-intermediate S. aureus (VISA), and vancomycin-resistant S. aureus (VRSA) isolates. LTX-109 demonstrated a MIC range of 2 to 4 μg/ml and dose-dependent rapid bactericidal activity against S. aureus. This activity was not influenced by resistance to other antistaphylococcal agents.